Literature Review: Pengaruh Volume Prostat terhadap Kejadian Retensi Urin Akut pada Pasien BPH - Zahra Fauziya; Hendra Sutapa; Dewi Indah Noviana Pratiwi (Homeostasis, 2021)
Abstract: Benign prostatic hyperplasia (BPH) is a hyperplasia of prostate cells. Acute urinary retention is a common complication of BPH. This literature review aims to give some insights regarding the effects of prostate volume on the incidency of acute urinary retention by observing the mean of prostate volume and incidency of acute urinary retention in BPH patients. The source of this study is nine journals related to the topic from some medical journal database: PubMed, Science Direct and Google Scholar. The writer compiled some journals in English and Bahasa Indonesia which were published in 2010-2020. The study shows that 8 out of 9 researches indicate that prostate volume has an effect on the incidency of acute urinary retention in patients with benign prostatic hyperplasia (BPH). The mean volume of prostate in patients with BPH is 53,9 ml. 470 out of 2464 patients with BPH in this study developed acute urinary retention.  Keywords: effect, prostate volume, acute urinary retention, benign prostatic hyperplasia, BPH. Abstrak: Benign prostatic hyperplasia (BPH) merupakan hiperplasia sel kelenjar prostat. Retensi urin akut merupakan salah satu komplikasi yang umum terjadi pada pasien BPH. Literature review ini disusun guna menambah wawasan mengenai pengaruh volume prostat terhadap kejadian retensi urin akut pada pasien BPH dengan melihat gambaran rerata volume prostat dan kejadian retensi urin akut pada pasien BPH. Sumber literatur berupa sembilan jurnal terkait yang diperoleh melalui database jurnal kedokteran, yaitu PubMed, Science Direct dan Google Scholar. Penulis mengambil jurnal dengan bahasa inggris maupun bahasa Indonesia yang dipublikasi dalam kurun waktu 2010-2020. Hasil yang didapat dari studi ini adalah 8 dari 9 penelitian yang ditinjau mengindikasikan terdapat pengaruh volume prostat terhadap kejadian retensi urin akut pada pasien benign prostatic hyperplasia (BPH). Rerata volume prostat dari pasien benign prostatic hyperplasia (BPH) adalah 53,9 ml. Terdapat 470 dari total 2464 pasien BPH pada literatur yang mengalami retensi urin akut. Kata-kata kunci:         pengaruh, volume prostat, retensi urin akut, benign prostatic hyperplasia, BPH.